1996
DOI: 10.1161/01.atv.16.2.328
|View full text |Cite
|
Sign up to set email alerts
|

Only the Two End Helixes of Eight Tandem Amphipathic Helical Domains of Human Apo A-I Have Significant Lipid Affinity

Abstract: Human apolipoprotein A-I (apo A-I) possesses multiple tandem repeating 22-mer amphipathic alpha-helixes. Computer analysis and studies of model synthetic peptides and recombinant protein-lipid complexes of phospholipids have suggested that apo A-I interacts with HDL surface lipids through cooperation among its individual amphipathic helical domains. To delineate the overall lipid-associating properties of apo A-I, the first step is to understand the lipid-associating properties of individual amphipathic helica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
191
1
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 209 publications
(208 citation statements)
references
References 45 publications
15
191
1
1
Order By: Relevance
“…The first amyloidogenic segment (residues [14][15][16][17][18][19][20][21][22] in the N-terminal region contains very hydrophobic amino acids (LATVYVDVL), overlapping with the hydrophobic helix-forming region upon lipid binding of apoA-I [26,27]. The deletion of the extreme N-terminal residues 1-43 was shown to destabilize the N-terminal helix bundle structure and induce a large reduction in the enthalpy of lipid binding of full-length apoA-I [17,28], indicating critical roles of the 1-43 segment in the lipid-free conformation and lipid interaction of apoA-I.…”
Section: Discussionmentioning
confidence: 99%
“…The first amyloidogenic segment (residues [14][15][16][17][18][19][20][21][22] in the N-terminal region contains very hydrophobic amino acids (LATVYVDVL), overlapping with the hydrophobic helix-forming region upon lipid binding of apoA-I [26,27]. The deletion of the extreme N-terminal residues 1-43 was shown to destabilize the N-terminal helix bundle structure and induce a large reduction in the enthalpy of lipid binding of full-length apoA-I [17,28], indicating critical roles of the 1-43 segment in the lipid-free conformation and lipid interaction of apoA-I.…”
Section: Discussionmentioning
confidence: 99%
“…A continuous helix repeat assignment describes 10 tandemly repeated helices punctuated mainly by prolines. However, although this continuous helical model is the most widely used one, assignment of the precise secondary structural distribution throughout the apoA-I sequence is far from agreement by different approaches [11,[15][16][17][18][19][20][21][22] Thus, studies of peptides [15,[23][24][25] that model different regions of apoA-I can provide important information on the roles of specific residues and segments, and their interactions in the structure and stability of the parent apolipoprotein. Analysis of the consensus sequences of the A and B repeat derived from the sequences of multiple exchangeable apolipoproteins [7], together with studies of 44-residue consensus sequence peptides, showed ~ 90% and 5 0% α-helical contents for peptides with ABAB [26] and ABBA [27] sequence ordering respectively.…”
mentioning
confidence: 99%
“…Studies have revealed that the N-terminal region of apoA-I plays an important role in initiating lipid binding and the formation of nascent HDL (3). The central region (residues 144-186) was the key domain for the activation of LCAT (4,5) and was also important for the maturation and stability of HDL (6).…”
mentioning
confidence: 99%